Bakso Go Online: Inisiatif Promosi Digital dan Pembayaran QRIS bagi Pedagang Kaki Lima - Maria Atik Sunarti Ekowati; Kristyana Dananti; Sri Wening (CV. KAMPUS AKADEMIK PUBLISING, 2025)
his Student Creativity Program (PKM) aims to empower street meatball vendors through digital transformation based on online promotion and the use of the non-cash payment system, QRIS. The partners in this activity are groups of street meatball vendors in the [name of city/subdistrict] area, most of whom have not yet utilized digital media for marketing and still rely on cash transactions. The problems faced by the partners include limited ability to reach customers online, low understanding of digital marketing, and limited access to digital payment technologies.The solutions offered in this program include training in promotion via social media (Instagram, WhatsApp Business, and Google Maps), the creation of simple promotional content, and assistance in activating and using QRIS. Conceptually, this program adopts a state-of-the-art approach to the implementation of micro digital marketing and QR-based payment systems (Quick Response Code Indonesian Standard) as a strategic step for MSME adaptation to the Industry 4.0 era and post-pandemic conditions. The urgency of this activity lies in the need to enhance the competitiveness of informal micro-entrepreneurs so they can survive and grow through the adoption of affordable and accessible digital technologies. The implementation method includes field observation, hands-on training, creation of visual promotional materials, and regular post-training monitoring and evaluation. The results show an increase in the partners’ understanding of digital media, the creation of active social media promotional accounts, and the successful use of QRIS as an alternative payment method by customers. The outputs produced from this program include: (1) a PKM report, (2) a community service scientific article, (3) an educational documentation video, and (4) social media accounts for product promotion by partners. This activity is expected to serve as a replicable model for empowering informal sector MSMEs.